Isolated left bronchial isomerism that was incidentally detected as a severe obstructive ventilatory disturbance in an asymptomatic adult patient: A case report. Issue 22 (29th May 2020) - Heo, Manbong; Jeong, Jong Hwan; You, Jung Wan; Kim, Ju-Young; Park, Mi Jung; Jeon, Kyung Nyeo; Lee, Jong Deog; Lee, Seung Jun
Abstract: Rationale: Left bronchial isomerism is generally associated with abnormal arrangement of the atrium and abdominal viscera; therefore, its diagnosis is confirmed in early childhood. Patient concerns: Here we report a rare case involving a 36-year-old man with isolated left bronchial isomerism that presented as an asymptomatic severe obstructive ventilatory disturbance during pulmonary function tests performed as part of routine assessments for an orbital wall fracture. The patient was a current smoker and did not show any respiratory symptoms. Diagnosis: Chest computed tomography revealed left bronchial isomerism, and further tests showed that there was no involvement of other organs. Interventions: We recommended smoking cessation and the long-term use of an inhaled long-acting bronchodilator. Outcomes: The findings from this case highlight the causative role of left bronchial isomerism in asymptomatic adults with chronic obstructive pulmonary disease. Lessons: Physicians should consider this condition as a cause of obstructive ventilatory disturbances in asymptomatic adult patients.